Shaping Futures for the Hotel Industry: Certified Internships and Commitment Toward Career Development - Ferdian, Feri; Yulastri, Asmar; Mohd Zahari, Mohd Salehuddin; Suyuthie, Hijriyantomi; Pasaribu (Journal of Technical Education and Training, 2025)
This scholarly investigation explores the impact of hotel industry hallmarks, internship service quality, and the mediating role of mentorship on undergraduate hotel management students’ commitment toward careers in the hospitality industry. A quantitative, cross-sectional design utilizing a self-administered survey questionnaire was employed. The sample and unit of analysis comprised hotel management students from Universitas Negeri Padang, West Sumatera, Indonesia, who had completed certified internship programs. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test the proposed hypotheses. The findings revealed that the hallmarks of the hotel industry such as demanding work environments, extensive responsibilities, limited career advancement, and minimal recognition did not exert a negative influence on students’ commitment toward career. Conversely, the quality of internship service experience exhibited a strong positive effect on students’ professional commitment. The study also established a causal relationship between industry hallmarks, service quality, and mentorship. Notably, mentorship was found to significantly mediate the relationships between both hallmarks and service quality with students’ commitment toward career. These findings offer critical insights and carry significant implications for students, academic institutions, industry practitioners, and policymakers.